Thermal and energy performance of an integrated hybrid radiant-convective heating system in office cubicles - Fatih Evren (Case Studies in Thermal Engineering, 2025)
Open offices are preferred in office buildings due to cost advantages, space efficiency, and increased productivity. However, different thermal comfort perceptions among employees in such environments often lead to hindering satisfaction and productivity while reducing energy efficiency. Operative temperature, the fundamental comfort temperature for the human body, depends on parameters like radiative and convective components, clothing, and activity levels. This study integrates a hybrid heating system into office cubicles to create individual comfort zones and experimentally investigates energy consumption. The hybrid system, featuring radiative panels with electric film heaters and electric convective components, allows independent control of the operative temperature's radiative and convective elements. Experiments were conducted in a typical office with two cubicles; one is active, and the other is passive. Operative temperature is measured over black globe temperature, air temperature, and airspeed measurements. Vertical air temperatures were measured at four points at three levels within the individual comfort zone. The hybrid system achieved a 1 °C operative temperature increase in the cubicle with a 0.5 kW consumption rate, corresponding to 40 % less energy consumption compared to the central convective system.